Title: p38δ Regulates IL6 Expression Modulating ERK Phosphorylation in Preadipocytes - Díaz-Chamorro, Selene; Garrido-Jiménez, Sergio; Barrera-López, Juan Francisco; Mateos-Quirós, Clara María; Cumplido-Laso, Guadalupe; Lorenzo, María Jesús; Román, Ángel Carlos; Bernardo, Edgar; Sabio, Guadalupe; Carvajal-González, José María; Centeno, Francisco (Frontiers in Cell and Developmental Biology, 2022)
IL6 is an essential cytokine in metabolism regulation and for intercommunication among different organs and tissues. IL6 produced by different tissues has different functions and therefore it is very important to understand the mechanism of its expression in adipose tissue. In this work we demonstrated that IL6 expression in mouse preadipocytes, like in human, is partially dependent on Wnt5a and JNK. Using mouse preadipocytes lacking each one of the p38 SAPK family members, we have shown that IL6 expression is also p38γ and p38δ dependent. In fact, the lack of some of these two kinases increases IL6 expression without altering that of Wnt5a. Moreover, we show that the absence of p38δ promotes greater ERK phosphorylation in a MEK 1/2 independent manner, and that this increased ERK phosphorylation state is contributing to the higher IL6 expression in p38δ-/- preadipocytes. Finally, we have shown a new crosstalk between two MAPK signaling pathway, p38δ and ERK, p38δ might activate a serine-threonine phosphatase which would modulate the phosphorylation state of ERK